Muscle oxygenation asymmetry in ice speed skaters: Not compensated by compression - Born, D.-P.; Zinner, C.; Richter, K.; Holmberg, H. C.; Sperlich, B. (International Journal of Sports Physiology and Performance, 2014)
Purpose: The current investigation assessed tissue oxygenation and local blood volume in both vastus lateralis muscles during 3000-m race simulations in elite speed skaters on ice and the effects of leg compression on physiological, perceptual, and performance measures. Methods: Ten (6 female) elite ice speed skaters completed 2 on-ice trials with and without leg compression. Tissue oxygenation and local blood volume in both vastus lateralis muscles were assessed with near-infrared spectroscopy. Continuous measures of oxygen uptake, ventilation, heart rate, and velocity were conducted throughout the race simulations, as well as blood lactate concentration and ratings of perceived exertion before and after the trials. In addition, lap times were assessed. Results: The investigation of tissue oxygenation in both vastus lateralis muscles revealed an asymmetry (P < .00; effect size = 1.81) throughout the 3000-m race simulation. The application of leg compression did not affect oxygenation asymmetry (smallest P = .99; largest effect size = 0.31) or local blood volume (P = .33; 0.95). Lap times (P = .88; 0.43), velocity (P = .24; 0.84), oxygen uptake (P = .79; 0.10), ventilation (P = .11; 0.59), heart rate (P = .21; 0.89), blood lactate concentration (P = .82; 0.59), and ratings of perceived exertion (P = .19; 1.01) were also unaffected by the different types of clothing. Conclusion: Elite ice speed skaters show an asymmetry in tissue oxygenation of both vastus lateralis muscles during 3000-m events remaining during the long gliding phases along the straight sections of the track. Based on the data, the authors conclude that there are no performance-enhancing benefits from wearing leg compression under a normal racing suit.